Socio-Economic Impact of BP Koirala Institute of Health Sciences on Dharan Town Over the last 20 Years - Jha, N; Sharma, KR; Niraula, SR; Ghimire, A; Yadav, DK; Singh, SB (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Socio-economic changes are constantly occurring in various societies with multiple reasons. Sometimes, the initiation of an educational institution, especially colleges and universities, can have a profound impact on the economy of a town. B. P. Koirala institute of Health sciences (BPKIHS) has been in existence in Dharan since 1993 (a joint project of Government of Nepal and Government of India) and it has been more than its 25 successful years. Objectives: To examine the role of BPKIHS in changing socio-economic status of Dharan town, and to compare health and economic indicators in various cities like Dharan, Rajbiraj, Birganj, Pokhara and Nepalganj. Methodology: Both quantitative and qualitative methods were used in this study to assess health and socioeconomic conditions. Information from Dharan was collected through Quantitative methods like Household Survey and Collection of Secondary Data, and Qualitative methods like Focus Group Discussion (FGD) and Interview with Key Informants. Similarly in Rajbiraj, Birganj, Pokhara and Nepalganj; secondary data and interview with key informants were used for gathering information. Results: A total of 1500 households with 7198 population were surveyed in all 19 wards of Dharan. The rent of houses has increased significantly (p < 0.001) along with the use of items like electricity, radio, television, telephone, motor vehicle, bicycle, computer and gas-stoves compared to 22 years back in Dharan, which is statistically significant. Most (85.6%) of the people of Dharan go to BPKIHS for treatment and about three quarters (73.1%) of the surveyed household reported improvement in health status. More than 70% household reported improvement in socio-economic status of the people of Dharan due to the establishment of the BPKIHS. Comparing records and reports provided by various offices (secondary data) of Dharan, Rajbiraj, Birganj, Pokhara and Nepalganj, remarkable progress is seen in the developmental indicators of Dharan. Likewise key informant interview revealed noteworthy development in Dharan compared to the other four towns, predominantly due to the presence of BPKIHS, while industry/business and tourism were responsible in other towns. The participants of FGDs stated that the existence of the BPKIHS is one among the first three factors responsible for the socio-economic development of Dharan. They also reported that health, education and tourism of the town have been greatly influenced by the presence of the BPKIHS. Conclusion: BPKIHS has made a great impact in the improvement of health and economic status of the people of Dharan. This survey revealed a positive attitude of the people towards BPKIHS. The future calls for a hand in hand approach with local population and dissemination of up to date and efficient services to further improve socioeconomic and health status of the people of Dharan.